2022
DOI: 10.1038/s41592-022-01624-x
|View full text |Cite
|
Sign up to set email alerts
|

SyConn2: dense synaptic connectivity inference for volume electron microscopy

Abstract: The ability to acquire ever larger datasets of brain tissue using volume electron microscopy leads to an increasing demand for the automated extraction of connectomic information. We introduce SyConn2, an open-source connectome analysis toolkit, which works with both on-site high-performance compute environments and rentable cloud computing clusters. SyConn2 was tested on connectomic datasets with more than 10 million synapses, provides a web-based visualization interface and makes these data amenable to compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Previous machine learning methods for neuropil annotation have primarily used features that were hand-designed or derived from supervised learning, including random forests trained on hand-designed features 9,21 , 2d convolutional networks trained on projections of neuropil ("Cellular Morphology Networks") 22,23 , point cloud networks trained on representations of cell membranes 24 , or 3d convolutional networks trained directly on voxels 25 . Schubert et al 22,24 trained cell representations using a triplet loss, but it was not reported whether these representations are suitable for downstream analyses. Previous results on cell type classification of neurite fragments required larger spatial context, precomputed organelle masks, and manually engineered features [21][22][23][24] , or used a single local view to achieve modest classification accuracy on a limited set of classes 22 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous machine learning methods for neuropil annotation have primarily used features that were hand-designed or derived from supervised learning, including random forests trained on hand-designed features 9,21 , 2d convolutional networks trained on projections of neuropil ("Cellular Morphology Networks") 22,23 , point cloud networks trained on representations of cell membranes 24 , or 3d convolutional networks trained directly on voxels 25 . Schubert et al 22,24 trained cell representations using a triplet loss, but it was not reported whether these representations are suitable for downstream analyses. Previous results on cell type classification of neurite fragments required larger spatial context, precomputed organelle masks, and manually engineered features [21][22][23][24] , or used a single local view to achieve modest classification accuracy on a limited set of classes 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Schubert et al 22,24 trained cell representations using a triplet loss, but it was not reported whether these representations are suitable for downstream analyses. Previous results on cell type classification of neurite fragments required larger spatial context, precomputed organelle masks, and manually engineered features [21][22][23][24] , or used a single local view to achieve modest classification accuracy on a limited set of classes 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Next we automated the detection of synaptic features. For this task, we used the SyConn v.2 pipeline 41,42 . We first used a deep neural network to map synaptic clefts and vesicle clouds (Fig.…”
Section: A Digital Address Book For All Neurons and Their Connectionsmentioning
confidence: 99%
“…We used SyConn2 (ref. 42 ) to process the automatic synaptic cleft, synaptic vesicle cloud and neurite segmentations and generate a synaptic connectome. The respective processing parameters and a source code snapshot can be found under https://gitlab.mpcdf.mpg.de/pschuber/ SyConn/-/tree/chunk_mask.…”
Section: Mapping Of Automatic Synapse Detection To Neurite Segmentationmentioning
confidence: 99%
“…This contrasts with the crucial functional reliance of neurons and synapses on their specific molecular machineries, reflected in enormous molecular diversity both at cellular and synaptic levels. EM reconstructions do allow inferring connectivity via chemical synapses from structural features with high accuracy (14)(15)(16)(17)(18). However, they are incomplete in the sense that in pure EM data, these cannot be further differentiated molecularly and information related to other forms of signaling between cells, like the distribution of receptor molecules beyond classical synaptic transmission, remains hidden.…”
mentioning
confidence: 99%